1995
DOI: 10.1016/0014-5793(95)00713-j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two highly homologous presynaptic proteins distinctly localized at the dendritic and somatic synapses

Abstract: Through screening of a murine brain cDNA library, we have isolated two brain specific cDNAs encoding highly homologous proteins, named 921-L and 921-S, comprised of 134 amino acids with 80% identity. Immunohistological study with the mAbs raised against the bacterially expressed 921 proteins showed that 921-L protein is distributed at the dendritic region and 921-S at the neuronal somatic surface. Immuno-electron microscopic study revealed that both 921 proteins are localized at the presynaptic terminal, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(19 citation statements)
references
References 24 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…The AH motif was initially identified by inspection of the CPX-1 sequence (Wragg et al, 2013), though a similar sequence was noted in mammalian complexins by others (Takahashi et al, 1995; Seiler et al, 2009). We confirmed membrane-association of the AH motif using NMR binding assays, and demonstrated that the AH motif becomes helical upon binding to highly curved liposomes using a combination of CD spectroscopy and mutational analysis (Seiler et al, 2009; Wragg et al, 2013; Snead et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…The AH motif was initially identified by inspection of the CPX-1 sequence (Wragg et al, 2013), though a similar sequence was noted in mammalian complexins by others (Takahashi et al, 1995; Seiler et al, 2009). We confirmed membrane-association of the AH motif using NMR binding assays, and demonstrated that the AH motif becomes helical upon binding to highly curved liposomes using a combination of CD spectroscopy and mutational analysis (Seiler et al, 2009; Wragg et al, 2013; Snead et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…These protein complexes were confirmed by both 2-D BN/SDS-PAGE and co-IP assays. While SNARE-Cplx1 oligomers were expected (63; 64), SNAP25-VAMP dimers were a surprise. In SNARE assembly, t-SNAREs (Stx1-SNAP25) are formed first, and v-SNAREs (VAMP) are attached later (61).…”
Section: Discussionmentioning
confidence: 98%
“…Cplx1 is mainly expressed in inhibitory neurons, while excitatory terminals are enriched in Cplx2 (63; 64). Orbitofrontal GABAergic, but not glutamatergic neurons may display aberrant SNARE complex activity, which could result in constitutive inhibition of the glutamate system, and perhaps contribute to lower OFC function (8).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adult mammalian retinal ribbon synapses selectively express the complexin 3/4 subfamily [22,23]. The mammalian complexins are a family of small, hydrophilic proteins encoded by four genes that can be grouped into two subfamilies based upon sequence identity and expression patterns [23-26]. Complexins 1 and 2 share approximately 80% amino acid identity and are enriched at conventional synapses [24-26], where they appear to activate and stabilize the SNARE complex in a fusion-ready state before calcium enters the terminal and binds to synaptotagmin (reviewed in [27]).…”
Section: Introductionmentioning
confidence: 99%